Disturbance‐modulated symbioses in termitophily. Issue 24 (9th November 2017) - Monteiro, Ivan; Viana‐Junior, Arleu Barbosa; de Castro Solar, Ricardo Ribeiro; de Siqueira Neves, Frederico; DeSouza, Og
Abstract: Symbiosis, the living‐together of unlike organisms, underlies every major transition in evolution and pervades most ecological dynamics. Among examples of symbioses, the simultaneous occupation of a termite nest by its builder termites and intruding invertebrate species (so‐called termitophily) provides suitable macroscopic scenarios for the study of species coexistence in confined environments. Current evidence on termitophily abounds for dynamics occurring at the interindividual level within the termitarium, but is insufficient for broader scales such as the community and the landscape. Here, we inspect the effects of abiotic disturbance on termitophile presence and function in termitaria at these broader scales. To do so, we censused the termitophile communities inhabiting 30 termitaria of distinct volumes which had been exposed to increasing degrees of fire‐induced disturbance in a savanna‐like ecosystem in southeastern Brazil. We provide evidence that such an abiotic disturbance can ease the living‐together of termitophiles and termites. Putative processes facilitating these symbioses, however, varied according to the invader. For nonsocial invaders, disturbance seemed to boost coexistence with termites via the habitat amelioration that termitaria provided under wildfire, as suggested by the positive correlation between disturbance degree and termitophile abundance and richness. As for social invaders (ants), disturbance seemed to enhance associational defenses with termites, as suggested by the negative correlation between the presence of ant colonies and the richness and abundance of other termitarium‐cohabiting termitophiles. It is then apparent that disturbance‐modulated distinct symbioses in these termite nests. Abstract : Fire‐induced disturbance boosted coexistence of termites and non‐social termitophiles via the habitat amelioration that termitaria provided under wildfire. Simultaneously, harsh conditions enhanced termitaria defense by social termitophiles (ants).